Strategie ambidestre e crisi economica: le peculiarità della piccola impresa - Cesaroni, Francesca Maria; Sentuti, Annalisa (Piccola Impresa / Small Business, 2016)
The paper aims to examine how ambidextrous strategies can be effectively adopted by small businesses to face the economic crisis. Ambidextrous strategies combine defensive and offensive approach, retrenchment and investment/innovation, short- and long-term perspective. According to the main literature, ambidextrous strategies are more likely to be successful in an economic downturn.Nevertheless, they are considered a challenge for small businesses, which have often limited financial and managerial resources, especially during an economic crisis.Through the analysis of a “prelude case”, small businesses’ approach for ambidextrous strategies to deal with economic crisishas been identified, together with factors and conditions (necessary or facilitating)that can favor small firms to adopt these strategies.